Patient and family perceptions of hospice services: 'I knew they weren't like hospitals' - Bray Y; Goodyear-Smith F (CSIRO Publishing, 2013)
INTRODUCTION: The vision for palliative care service provision in New Zealand is for all people who are dying and their families to have timely access to culturally appropriate, quality palliative care services. An Auckland hospice's records show that the ethnically diverse population statistics were not reflected in the referrals for hospice services. The aim of this research was to gain a patient-and-their-family perspective on the hospice, including exploration of components of service care that could be improved for various cultural groups. METHODS: Patients currently under the care of the hospice and family members were recruited from hospice records. Semi-structured interviews were conducted to explore the emerging issues. The study collected data from a purposive sample of 18 palliative care patients or carer family members, ranging in age from 39 to 81 years, who reflected the ethnic diversity of the population of the region. Interviewing was carried out by an experienced research assistant and continued until data saturation was reached. FINDINGS: Four key themes emerged-hospice personnel's approach to patients, quality of service, cultural barriers, and strategies for future improvement. It was determined that the latter two were the most significant to address in this article. CONCLUSION: The study revealed the need for information-giving and education, including public profiling of the hospice to strengthen community involvement. Strategies to reduce ethnic disparities include strengthening the awareness of, and access to, services by connecting with cultural groups through churches, community and specific cultural media.